2013
DOI: 10.1371/currents.dis.2664354a5571512063ed29d25ffbce74
|View full text |Cite
|
Sign up to set email alerts
|

The Human Impact of Tropical Cyclones: a Historical Review of Events 1980-2009 and Systematic Literature Review

Abstract: Background. Cyclones have significantly affected populations in Southeast Asia, the Western Pacific, and the Americas over the past quarter of a century. Future vulnerability to cyclones will increase due to factors including population growth, urbanization, increasing coastal settlement, and global warming. The objectives of this review were to describe the impact of cyclones on human populations in terms of mortality, injury, and displacement and, to the extent possible, identify risk factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 41 publications
1
68
0
2
Order By: Relevance
“…Other reviews have summarized the impact of flood or storm disasters on mortality and the causes, risk factors, or burden of specific diseases. [4][5][6][7] These approaches take a preventative public health perspective and are important for reducing a disaster's health impact.…”
Section: Introductionmentioning
confidence: 99%
“…Other reviews have summarized the impact of flood or storm disasters on mortality and the causes, risk factors, or burden of specific diseases. [4][5][6][7] These approaches take a preventative public health perspective and are important for reducing a disaster's health impact.…”
Section: Introductionmentioning
confidence: 99%
“…Developing countries with poor or non-existing civil registration systems are not represented, and our results should not be generalised to those countries. Indeed, it has been shown that flood and storm mortality is concentrated in the less developed and heavily populated nations of southeast Asia and the western Pacific (Doocy et al 2013a(Doocy et al , 2013b, where WHO data are scarcely available. The demographic differentials in flood-and storm-related mortality observed in this study could thus be biased.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to geophysical characteristics, the level of economic development has been found to be significant in determining human and economic losses from natural disasters (Fankhauser and McDermott 2014;Toya and Skidmore 2007). Compared to more developed countries, developing countries generally suffer much higher death tolls from floods and cyclones because they often have poor infrastructure and badly constructed housing, high-density settlements, a lack of early warning systems, and poorly devised evacuation and shelter procedures (Doocy et al 2013a). The fact that most deaths from cyclones in less developed nations are storm surge drowning fatalities that occur during the impact phase implies that deaths from storms are, to a certain degree, preventable (Shultz et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is estimated that 10,000 people have died every year since 1980 due to tropical cyclones 94 (Doocy et al 2013), and thus it is of great importance to study tropical cyclones and to 95 understand their response to changes in environmental conditions such as sea surface 96 temperature (SST). The sensitivity of frequency, intensity, and duration of tropical 97 cyclones to climate change has been extensively investigated with a general conclusion 98 that both global and regional changes in TC behavior should be expected as the climate 99 and SST change (e.g., Emanuel heat into the Northeastern Pacific basin to directly fuel intense hurricanes in that basin 135 two or three seasons after its winter peak.…”
mentioning
confidence: 99%